(untitled) (The International Conference on Sustainable Economics Management and Accounting Proceeding, 2025)
The green economy is a global concern in sustainable development as it provides an approach that combines economic growth with environmental conservation. However, not all countries have managed to optimize the contribution of the green sector to economic income. This study aims to analyze the effect of several green economy indicators and other economic factors such as renewable energy, carbon emissions, nuclear energy, population, and foreign direct investment on Gross Domestic Product (GDP) in five OECD member countries in 2008-2023. This study uses quantile panel regression analysis tool. The regression results show that renewable energy variables are only significant in the middle and upper quantiles (0.50 and 0.75), while carbon emissions and population have significant positive effects in all quantiles, namely low, medium and high. Nuclear energy has a significant negative effect, while FDI has no effect and tends to have a negative impact on GDP. The contribution of green economy variables to economic growth varies depending on the income level of the country. Therefore, green economy policies need to be tailored to the economic characteristics of each country to be more effective in promoting sustainable growth.